2017
DOI: 10.18203/2349-3933.ijam20172269
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nevirapine vs efavirenz containing regimens on clinical outcomes among HIV patients on ART: a comparative study

Abstract: Background: The present study has been conducted to compare regimens containing either of nevirapine (NVP) and efavirenz (EFV) and two or more nucleoside reverse transcriptase inhibitors (NRTIs) among HIV infected patients in respect to clinical outcome and to compare incidence of opportunistic infections among these patients.Methods: This study was an observational study conducted at a tertiary care centre over 105 patients, who were evenly matched and received three antiretroviral drug one of the drug was ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…5. Whereas the studies conducted by Melkamu, Rajput, and Solomon reported TB (29.8%) was the most common OI, which is similar to the study conducted by 9,17,18 .…”
Section: Prevalence Of Opportunistic Infections (Oi's)supporting
confidence: 75%
“…5. Whereas the studies conducted by Melkamu, Rajput, and Solomon reported TB (29.8%) was the most common OI, which is similar to the study conducted by 9,17,18 .…”
Section: Prevalence Of Opportunistic Infections (Oi's)supporting
confidence: 75%
“…While in developing country like India nevirapine based HAART is cheap compared to efavirenz based therapy. 11…”
Section: Discussionmentioning
confidence: 99%